Evaluation of target achievement of overburden removal at PT Madurejo Jaya Utama - Ahsan Derajat Bimantara; Riswan Riswan; Karina Shella Putri (Jurnal Himasapta, 2026)
Pengupasan lapisan overburden merupakan kegiatan penting pada operasi tamabng terbuka. Penelitian ini bertujuan untuk mengevaluasi produksi alat gali muat dan alat angkut dan kinerjanya dalam mencapai target pembongkaran overburden. Metode pengumpulan data dilakukan dengan pengamatan di lapangan yaitu cycle time alat angkut, cycle time alat angkut, dan kondisi loading point. Data sekunder yang diperoleh dari perusahaan yaitu spesifikasi alat, bucket fill factor, target produktivitas, dan swell factor. Pengolahan data berupa perhitungan produktivitas alat gali muat dan alat angkut serta match factor. Berdasarkan perhitungan data yang diambil dari lapangan, produktivitas alat gali muat dan alat angkut tidak mencapai target. Rata-rata produktivitas alat gali muat dengan jumlah passing 2 kali dan 3 kali ke setiap alat angkut adalah 302.84 bcm/jam dan 423.79 bcm/jam. Rata-rata produktivitas alat angkut dengan jumlah passing 2 kali dan 3 kali ke setiap alat angkut adalah 100.94 bcm/jam dan 141.27 bcm/jam. Alat gali muat dan alat angkut tidak mampu mencapai target produktivitas yang direncanakan oleh perusahaan yaitu 480 bcm/jam untuk alat gali muat dan 160 bcm/jam untuk alat angkut. Hasil analisis match factor, 0.70 dan 0.99, menunjukkan bahwa diperlukan alat angkut tambahan atau perbaikan cycle time pemuatan untuk meningkatkan produktivitas fleet/pasangan alat. Kata-kata kunci: produktivitas, cycle time, alat gali muat, alat angkut, passingABSTRACTOverburden stripping is a critical activity in surface mining operations. This study evaluates the productivity and performance of loading and hauling equipment in achieving the planned overburden removal target. Primary data were collected through field observations, including loading and hauling cycle times and loading point conditions. Secondary data obtained from the company included equipment specifications, bucket fill factor, productivity targets, and swell factor values. Equipment productivity and match factor were calculated to assess fleet performance. The results show that neither the loading nor hauling equipment achieved the company’s productivity targets. The average productivity of the loading equipment under two-pass and three-pass loading configurations was 302.84 bcm/h and 423.79 bcm/h, respectively. The corresponding average productivity of the hauling equipment was 100.94 bcm/h and 141.27 bcm/h. These values were below the planned targets of 480 bcm/h for loading equipment and 160 bcm/h for hauling equipment. The calculated match factor values of 0.70 and 0.99 indicate an imbalance between the loading and hauling fleets, resulting in suboptimal equipment utilization. To improve fleet performance and increase overburden removal productivity, additional hauling units and/or improvements in loading cycle time are recommended. Key words: productivity, cycle time, loading equipment, hauling equipment, passing